Respuestas
Respuesta dada por:
0
3x + 1 = 7/4
3x = 7/4 - 1
3x = 7/4 -4/4
3x = 3/4
x = (3/4) / 3
x = 3/12
x = 1/4
Comprobacion
3(1/4) + 1 = 7/4
3/4 + 4/4 = 7/4
7/4 = 7/4
3x = 7/4 - 1
3x = 7/4 -4/4
3x = 3/4
x = (3/4) / 3
x = 3/12
x = 1/4
Comprobacion
3(1/4) + 1 = 7/4
3/4 + 4/4 = 7/4
7/4 = 7/4
Respuesta dada por:
0
Resolver.
3x + 1 = 7/4
3x = 7/4 - 1
3x = (7 - 4)/4
3x = 3/4
x = 3/4 : 3
x = 3/4 * 1/3
x = 3/12
x = 1/4
3x + 1 = 7/4
3x = 7/4 - 1
3x = (7 - 4)/4
3x = 3/4
x = 3/4 : 3
x = 3/4 * 1/3
x = 3/12
x = 1/4
Preguntas similares
hace 7 años
hace 7 años
hace 7 años
hace 9 años
hace 9 años
hace 10 años
hace 10 años